A Quantitative Assessment of Factors Affecting the Technological Development and Adoption of Companion Diagnostics - Luo, Dee; Smith, James A.; Meadows, Nick A.; Schuh, A.; Manescu, Katie E.; Bure, Kim; Davies, Benjamin; Horne, Rob; Kope, Mike; DiGiusto, David L.; Brindley, David A. (Frontiers in Genetics, 2016)
Rapid innovation in (epi)genetics and biomarker sciences is driving a new drug development and product development pathway, with the personalized medicine era dominated by biologic therapeutics and companion diagnostics. Companion diagnostics (CDx) are tests and assays that detect biomarkers and specific mutations to elucidate disease pathways, stratify patient populations, and target drug therapies. CDx can substantially influence the development and regulatory approval for certain high-risk biologics. However, despite the increasingly important role of companion diagnostics in the realization of personalized medicine, in the United States, there are only twenty-three Food and Drug Administration (FDA) approved companion diagnostics on the market for eleven unique indications. Personalized medicines have great potential, yet their use is currently constrained. A major factor for this may lie in the increased complexity of the companion diagnostic and corresponding therapeutic development and adoption pathways. Understanding the market dynamics of companion diagnostic/therapeutic (CDx/Rx) pairs is important to further development and adoption of personalized medicine. Therefore, data collected on a variety of factors may highlight incentives or disincentives driving the development of companion diagnostics. Statistical analysis for thirty-six hypotheses resulted in two significant relationships and thirty-four non-significant relationships. The sensitivity of the companion diagnostic was the only factor that significantly correlated with the price of the companion diagnostic. This result indicates that while there is regulatory pressure for the diagnostic and pharmaceutical industry to collaborate and co-develop companion diagnostics for the approval of personalized therapeutics, there seems to be a lack of parallel economic collaboration to incentivize development of companion diagnostics.